FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MENABUNG PADA BANK SYARIAH DI INDONESIA (META ANALISIS) - Ananda, Fitrotur Rafika; Clarashinta Canggih (Universitas Muhammadiyah Bengkulu, 2024)
The aim of this research is to analyze the factors that influence interest in saving at Islamic banks in Indonesia through a meta-analysis study.